On the health of staff of the provincial directorate of youth and sports during the COVID-19 epidemic: Researching the levels of physical activity and social media addiction - Böke, Hulusi (Progress in Nutrition, 2021)
Study Objectives: The aim of this study was to find out the physical activity and social media addiction levels of the personnel affiliated to the provincial directorate of youth and sports, while in the isolation conditions of the COVID-19 pandemic and to determine the correlation between these levels. Methods: A total of 271 individuals, including 166 women and 106 men, voluntarily participated in the study. T-test and Pearson’s correlation test were used to determine the direction and amount of the correlation for the dual data groups which show normal distribution, and the One-Way Anova test was applied to analyse the data sets with three or more groups. The Kruskal-Wallis test was used to analyse the data sets that have three or more groups that do not show normal distribution. SPSS and Jamovi package software’s were used in the analysis of the data obtained. Results: It was found out that the mean score of physical activity of the personnel was slightly above average and the social media dependency score was slightly below average. On the other hand, a significant and inverse correlation was found between means scores of physical activity and social media addiction. While the gender variable was found to be significant in both score types, it was understood that the job location variable was significant in terms of social media addiction score. Conclusion: It is recommended to organize activity and training programs in order to improve the physical activity level of the personnel and to decrease the social media consumption as well.